Modern Client Web-Technologies - Matvyi, Oleksandr; Melnyk, Halyna; Melnyk, Vasyl (My University, 2026)
The web has evolved into the central platform for delivering applications of every scale—from simple informational pages to complex systems used daily in finance, healthcare, communication, and entertainment. What distinguishes the modern web is not only its global reach but also the diversity of technologies that make rich, interactive, and secure applications possible. This textbook, Modern Client Web-Technologies, introduces students to the essential concepts and practices of today’s web development with a strong focus on the .NET ecosystem. While many resources describe web technologies in isolation, this book emphasizes how client-side applications interact with powerful backends, using .NET Web API as the foundation. Students will begin by exploring how to build and consume REST APIs, then move toward more flexible approaches such as GraphQL. Along the way, practical examples will show how authentication with JWT, real-time communication through WebSockets and webhooks, and the enforcement of security standards such as CORS fit into professional applications. Special attention is given to patterns for web development that help ensure maintainability and scalability, as well as practices like structured logging that support reliability in production environments. On the client side, two of the most widely adopted technologies—Blazor and React—will be presented. Students will learn how each framework approaches rendering, state management, and integration with APIs, gaining the ability to compare and evaluate them in different scenarios. The overarching goal of this textbook is not simply to provide a catalog of technologies, but to give students the skills to design and implement complete, modern web solutions. By working through real-world examples, students will understand how the pieces fit together: from building secure APIs, to connecting them with interactive client applications, to applying architectural patterns that keep projects manageable as they grow. In mastering these technologies, students will be prepared to build applications that are not only functional and efficient, but also secure, reliable, and futureproof—qualities that define professional web development today
Keywords: web; .net; blazor; graphql